Effect of Smoking on Coronary Artery Plaques in Type 2 Diabetes Mellitus: Evaluation With Coronary Computed Tomography Angiography - Jiang, Yu; Pang, Tong; Shi, Rui; Qian, Wen-lei; Yan, Wei-feng; Li, Yuan; Yang, Zhi-gang (Frontiers in Endocrinology, 2021)
Background: The effect of smoking on coronary artery plaques examined by coronary computed tomography angiography (CCTA) in type 2 diabetes mellitus (DM) is not fully understood. To explore the effect of smoking on coronary artery plaque by comparing characteristics of plaques between diabetes with and without smoking history and among different smoking durations. Materials and methods: In total, 1058 DM patients found to have coronary plaques on CCTA were categorized into smoker (n=448) and nonsmoker group (n=610). Smoker was stratified by smoking duration (≤20 years [n=115], 20~40 years [n=233] and >40 years [n=100]). Plaque types, luminal stenosis (obstructive [<50%] or nonobstructive [≥50%] stenosis), segment involvement score (SIS) and segment stenosis score (SSS) of CCTA data were compared among groups. Results: Compared to nonsmokers, smokers demonstrated increased odds ratio of noncalcified plaque (OR=1.423; P=0.014), obstructive plaque (OR=1.884; P<0.001), multivessel disease (OR=1.491; P=0.020), SIS≥4 (OR=1.662; P<0.001) and SSS≥7 (OR=1.562; P=0.001). Compared to diabetes with smoking duration ≤20 years, smoking duration of 20~40 years and >40 years had more mixed plaques (OR=2.623 and 3.052; Ps<0.001), obstructive plaques (OR=2.004 and 2.098; P=0.003 and 0.008; respectively), multivessel disease (OR=3.171 and 3.784; P<0.001 and P=0.001; respectively) and SSS≥7 (OR=1.605 and 1.950; P=0.044 and 0.020; respectively). Diabetes with smoking duration >40 years had more SIS≥4 (OR=1.900, P=0.034). Conclusion: Smoking is independently associated with presence of noncalcified, obstructive and more extensive coronary artery plaques in diabetes, and longer smoking duration is significantly associated with higher risk of mixed, obstructive and more extensive plaques